A single‐center experience using alemtuzumab, fludarabine, melphalan, and thiotepa as conditioning for transplantation in pediatric patients with chronic granulomatous disease. Issue 1 (10th October 2019) - Bhatt, Sima T.; Schulz, Ginny; Hente, Monica; Slater, Ashley; Murray, Lisa; Shenoy, Shalini; Bednarski, Jeffrey J.
Abstract: Chronic granulomatous disease (CGD) is an immune deficiency characterized by defective neutrophil function and increased risk of life‐threatening infections. Allogeneic hematopoietic cell transplantation is curative for CGD, and conditioning regimen impacts transplant‐related outcomes. We report a single‐center prospective study (NCT01821781) of four patients with CGD transplanted using a reduced‐intensity conditioning regimen (RIC) containing alemtuzumab, fludarabine, melphalan, and thiotepa. Patients had early immune reconstitution with low incidence of infections. Disease‐free survival was 75% at a median of five years after transplant. This RIC regimen presents an alternative approach for transplant of patients with CGD who may not tolerate busulfan‐based conditioning.